THE INFLUENCE OF THE AMOUNT OF COFFEE PRODUCTION, VALUE EXCHANGE AND INFLATION ON COFFEE EXPORTS INDONESIA 2016—2020 - Dian Rizky Amelia; Antoni Ludfi Arifin; Eric Hermawan (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
THE INFLUENCE OF THE AMOUNT OF COFFEE PRODUCTION, VALUE EXCHANGE AND INFLATION ON COFFEE EXPORTS INDONESIA 2016—2020